Basketball Games and Early Childhood Motoric Development: Systematic Literature Review - Oki Candra; Zulrafli Zulrafli; Tri Prasetyo; Gustiranda Gustiranda (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aims to examine literature that focuses on research on early childhood basketball learning and motor development. Using the search term "basketball game and children's motor development", two databases (Scopus and Google Scholar) were selected to select journal articles. To achieve the measurement objectives, the collected literature is examined using the Critical Appraisal table, then a comparison of the measurement results is carried out. Basketball games and children's motoric development are discussed in 17 literatures. The results of several journals revealed several significant things, including the fact that playing basketball improves students' motor skills by increasing movement speed, accuracy, and strength in static and dynamic spaces, as well as game performance. Basketball players compete at various levels of competition. In addition, children who previously experienced delays in these movements at the level of fitness, behavior, knowledge and basic skills, which include agility, balance and coordination, were greatly influenced by the basic movements and basic skills of mini basketball. Basketball also has many benefits for your health and happiness. It is considered an easy game to play because of the satisfying psychosocial interactions. generate profits that last into adulthood.